Pelatihan Pembuatan Pestisida Nabati Ramah Lingkungan di Desa Gambiran Kecamatan Mojoagung - Mis Suhartini; Aisa, Aufia; Lailatul Mathoriyah; Fauzan Achmada; Muchamad Rahman Bagus Tohari; Siti Fatimah; Ummi Karima (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
The lack of public understanding in the use of natural materials in making environmentally friendly pesticides is the basis for holding outreach to the Gambiran Village Farmers Group (POKTAN). Through this activity, it is hoped that farmers can increase their understanding of using natural materials to create works and not incur large costs because they can use materials that are easily accessible for products. This activity was carried out at the Gambiran village sports hall, Mojoagung Jombang on September 7, 2023. The target of this activity was the Gambiran Village farmer group with a total of 6 participants who were able to attend. This workshop and training was accompanied by resource person Mrs. Suhartini, SP, MM. as a lecturer at KH University. A. Wahab Hasbullah Jombang. The approach method in this activity includes lecture methods, discussions, question and answer sessions and practice in front of training participants directly. The results of this socialization received a positive response which can be seen from the results of the training, namely increasing the enthusiasm of residents to be enthusiastic about making vegetable pesticides.